A low cost cell calibration technique and its PC based control software - Ribeiro, A. Fernando (1997)
In this study, a technique will be presented to measure the absolute position of a robot and any other strategic positions within the workcell, and also its specially built control software. One of the most important factors affecting the absolute or world accuracy of robots is the variation in arm geometry from a perfect kinematics form. Since arm position is essentially controlled by means of joint angles, Cartesian co-ordinates of the tool centre point are derived from the forward kinematics transform equations assuming a perfect kinematics form. Any deviation from this perfect case will result in world positional errors and hence, for effective off-line programming it is important to calibrate the real robot hardware against the virtual model used by the robot simulation computer systems. This paper will report on work carried out in developing such low cost calibration technique, its PC Based control software and performance monitoring systems.